Pengaruh Media Karikatur Terhadap Kemampuan Menulis Slogan Siswa Kelas VIII SMP N 4 Lempuing Ogan Komering Ilir - Prayogi, Adi; Wardiah, Dessy; Agustina, Juaidah (Indo Green Journal, 2024)
This study aims to evaluate the effects of implementing cartoon media on the writing ability of eighth-grade students at SMP Negeri 4 Lempuing, Ogan Komering Ilir.This research was carried out because no one had conducted research to overcome the limitations of students' observations and thoughts that would be more focused through caricature media as a solution.Data was collected through tests, revealing that students engaged in learning with cartoon media achieved a higher average score (79.4) compared to the control group (70.7). Hypothesis analysis using t-statistic testing yielded a Thitung value of 5.10 with a ttable of 1.45. With the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0), it can be concluded that there is a significant influence of cartoon media on the writing ability of students in creating slogans. These findings support the idea that the use of cartoon images can enhance overall student engagement, correlating with positive outcomes in writing slogan texts. The implications of this research highlight the importance of considering innovative media strategies in the educational context to improve the writing skills of middle school students.